Zwalczanie drobnych kradzieży w polskim ustawodawstwie karnym oraz praktyce ścigania i orzecznictwa: The fight against petty larcenies in Polish penal legislation, prosecution and jurisdiction (Studia Prawnicze / The Legal Studies, 2023)
The study is concerned with the fight against petty larcenies of public anid private property. The “petty’ larcenies embrace both privileged types of effences (article 199 § 2 and 203 § 2 of the penal code) and misdemeanors (article 199 § 1 and 2 of the code of misdemeamors). The study is of historical and comparative nature and tackles two mutually interconnected themes: the legislative and penal policy. Accordingly, the development of the legislation related to petty larcenies is traced back to the enactment of the penal code in 1932, then the new code of penal law passed in 1969, as well as the law on misdemeanors of 1971. Next, against the background of statistical data, the main trends of prosecution policy and jurisdiction are presented. The successive legislative measures that result in practical trends have been shown against the background of political-criminal concepts prevailing in respective periods and relating to the prosecution of minor economic offences. Of special concern are the concepts that emerged in the sixties and are still topical at present. They have found their legislative manifestation in, among thers, the requalification of certain minor offences, larcenies included, into misdemeanors (the Act of June 16„ 1966), the enrich ed catalogue of penalties that do not require isolation (the penal cod of 1969) and the grounds for their adjudication, finally, the introduction of a new penal measure — a conditional discontinuance of legal proceedings — which could be availed of by courts and prosecutors.The mentioned legislation resulted in specific situation, since penal policy towards petty larcenies (similarly to other acts qualified as misdemeanors, but which still have their counterparts in penal code but are different from the latter in respect of quantitative properties) is carried out by three organs independently: courts, bodies of citizens having jurisdiction over minor offences, and prosecutors.The above statutory. “model” of fighting petty larcenies results as testified by empirical research, in several, frequently negative phenomena both in prosecution and jurisdiction, and has been critically assessed in the final party of the study. The assessment has been made in normative, criminological and penal-political terms, moreover, some postulates of changes have been directed to the legislator and the organs of the administration of justice.